Síntese de complexos de Ru(II) luminescentes: aplicações no combate à doença de Alzheimer - Almeida, Marlon Augusto Profeta de (2021)
Alzheimer’s disease (A.D) is the most common form of dementia affecting, especially, people with advanced age. There is no cure and the existing pharmaceuticals indicated for combating A.D act by inhibition of acetylcholinesterase enzyme (AChE), whose hyperactivity is related to the initial symptoms of the disease. This pharmaceuticals offer symptomatic and palliative treatments and are associated with several side effects. In this work two new Ru(II) compounds (RuFenGlic and RuEtPy) were designed to act as new AChE inhibitors. The complexes presented luminescence, being able to be used as luminescent probes for amyloid-β aggregation process which enables a potential diagnostic system. RuFenGlic complex showed poor inhibitory activity while RuEtPy complex showed inhibitory activity comparable to Galantamine drug. Furthermore, STD-1H-NMR analysis allowed inferring that Fen ligand of RuFenGlic complex and the EtPy ligand of RuEtPy complex are the most responsible for the inhibition observed for each complex. Photochemical properties of both complexes were studied in solution. RuFenGlic complex shows photostability when irradiated in wavelengths under its MLCT absorption band (420, 450, 520 nm). On the other hand, RuEtPy complex shows photosubstitution of the EtPy ligand when irradiated in the same wavelengths. The phenomenon is observed by MLCT shifts and sequential luminescence quenching after irradiation. Interestingly, this photochemical reaction for this complex reaches stabilization after 3 hours of irradiation, with substitution of only one of the EtPy ligands and luminescence quenching between 70 and 90% of the band, but never total quenching. This property can be explored for diagnose and treatment of cancer through photoactivatable chemotherapy (PACT).